Prospecção de substâncias com atividade antagonista á Candida albicans produzida por bactéria endofítica da região amazônica - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The Amazon Biodiversity symbolize Is a great potential to Discovery of new bacterial straight producer of active biomolecules with importance biotechnological as antimycotics that can be producing by endophytic microorganisms whose the object may be the yeast Candida albicans. This yeast is present in the human body as commensally, being able to cause serious infections, especially in individual immune depressed by diseases as cancer, AIDS and diabetes. It is resistant to antifungal available actually. This way, the object this study was find, from the Amazon bacteria, a bacteria able of produce actives molecules against the C. Albicans yeast, with a purpose to make the production of a active extract that make possible to fractionate and purify the active substance. In the search this anti-candida substance after a analysis of bacteria from different habitats as Waters of the Rio Negro and Solimões and strains derived from endophytic bacteria work collection of Applied Genetics Laboratory Health and Biotechnology of UEA, initially had their potential antimicrobial tested against different pathogenic organisms (Mycobacterium smegmatis, Pseudomlmonasae ruginosa and Staphylococcus aureaus) by cross streaking. The potentials microorganisms were selected and identified by morphology and for sequences of the 16S rDNA region. The growth was made in two different culture media to production of crud extract. The verification the anti-candida action was by diffusion tests in Agar and the quantification was through the Minimum Inhibitory Concentration (MIC). The extract produced was pré-purified by chromatography in open column and was applied thin layer chromatography (TLC) to check the fractions obtained. In total six endopthytic bacteria were selected because they had antimicrobial activity against at least one of pathogens tested, but only the bacteria 229 presented active against C. albicans being cultivate to produce of extract and possibility of identified of anti-candida substance. The culture media that showed better production of biomolecules was the ISP2, according to analysis of size of the halos from of the extract produced. The colony growth was identified as B. amyloliquefaciens and morphologically characterized as Gram positive bacilli The pré-purification resulted in two actives fractions as MIC of 0,25 and 0,5 ug.mL-1 . This way, conclude that in Amazon is possible the identify of bacteria with pharmacological activities from which can be produce antimycotic molecules.
Keywords: Biodiversidade; Antimicótico; Bactéria endofítica; Biodiversity; Antifungal; Endophytic bacteria; CIÊNCIAS BIOLÓGICAS